2013
DOI: 10.2147/ijn.s40117
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun fiber membranes enable proliferation of genetically modified cells

Abstract: Polycaprolactone (PCL) and its blended composites (chitosan, gelatin, and lecithin) are well-established biomaterials that can enrich cell growth and enable tissue engineering. However, their application in the recovery and proliferation of genetically modified cells has not been studied. In the study reported here, we fabricated PCL-biomaterial blended fiber membranes, characterized them using physicochemical techniques, and used them as templates for the growth of genetically modified HCT116-19 colon cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 58 publications
(82 reference statements)
4
13
1
Order By: Relevance
“…As mentioned before, PCL have been reported as a low bioactive polymer [63]. Despite that, cell growth found for fibroblast exposed to pure PCL scaffolds is in accordance with growth promotion provoked by this polymer in other cells [88]. Some evidence of cell growth promotion is given for pure PCL, for example, it was reported that the proliferation rate of the PCL exposed HDF fibroblasts is higher than the normal growth tested after 3 days [89], moreover Safaeijavan et al [90] reported an increased proliferation of human fibroblast after been exposed to PCL electrospun scaffolds at 1-6 days.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…As mentioned before, PCL have been reported as a low bioactive polymer [63]. Despite that, cell growth found for fibroblast exposed to pure PCL scaffolds is in accordance with growth promotion provoked by this polymer in other cells [88]. Some evidence of cell growth promotion is given for pure PCL, for example, it was reported that the proliferation rate of the PCL exposed HDF fibroblasts is higher than the normal growth tested after 3 days [89], moreover Safaeijavan et al [90] reported an increased proliferation of human fibroblast after been exposed to PCL electrospun scaffolds at 1-6 days.…”
Section: Discussionsupporting
confidence: 64%
“…For that, the authors performed a cytotoxicity assay exposing NCTC clone 929 cells to PVP fragments and performed an irritability test by contact in New Zealand rabbits. They concluded that assessed polymeric materials did not present a toxic effect, demonstrating that these biomaterials can be used for the treatments of wounds in the form of advanced bandages or drug immobilization systems as transdermal therapeutic systems [88].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the variation of the melting point of P CL in the blend was monitored by varying the composition of CHT. Unlike other reported data [21,31,32,35], we found that by increasing CHT wt%, T m of the blend increased [51] except PCL/CHT 70/30.…”
Section: Microscopic Pcl/cht Chemical Structurecontrasting
confidence: 99%
“…Apart from the characteristic peaks of P CL and CHT, some other intense peaks were also detected due to the formation of different type of crystals with different D spacing within the crystal lattice [51]. Those gave an overall crystalline behaviour to the blend.…”
Section: Microscopic Pcl/cht Chemical Structurementioning
confidence: 99%